An Evaluation of the Adaptive Reuse of Abandoned Buildings - Hanieh Ahmadi Joshaghani; Mohammad Reza Hafezi; Behrooz Mohammad Kari (صفه)
Controlling the contaminants caused by the building industry has been one of the most significant concerns of the last decade. Like any other product, the making of a building takes raw materials and renewable and non-renewable energy, with the growth in development appearing to be inevitable particularly in the developing countries. The present research aims to determine the factors affecting the adaptive reuse of abandoned buildings, and compare the environmental impacts of reusing buildings with those of new constructions. Not every building is unreservedly suitable for reuse, though, and hence the necessity of decision tools to evaluate each building’s potential for reuse. For this purpose, the key criteria for the adaptive reuse of abandoned buildings were recognised and classified into seven categories. This was done through interviewing experts and library studies in the fields of energy and sustainability. The findings were then put into a questionnaire given to 110 experts, for them to evaluate the effectiveness any of these factors. The results were then analysed and the weight of decision criteria was determined using AHP method. According to the results, the affecting criteria were ranked as follows: environmental factors, architecture and urbanism, social, economic, physical, functional, and technology. In the end, the environmental factor was recognised as the most effective in the adaptive reuse of abandoned buildings, to decide whether to reuse or demolish a building.